Examining the Effect of Interest Rate Suppression on Credit Risk in the Banking Industry with a Focus on Financial Inclusion: A Simultaneous Equations Approach - Zafari, Elahe; Madanchi Zaj, Mahdi; Vakili Fard, Hamidreza; Khalili Araghi, Maryam (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: This study aims to examine the impact of interest rate suppression on credit risk in the banking industry, focusing on the moderating role of financial inclusion. Methodology: The study employed a two-stage least squares (2SLS) approach within a simultaneous equations framework, using panel data from 15 banks listed on the Tehran Stock Exchange over a nine-year period (2014–2022). Key variables, including non-performing loans (NPL), provisions for doubtful debts (BDTC), interest rate suppression (INDEX), and financial inclusion (OWN), were analyzed. Interaction terms were included to assess the moderating effects of financial inclusion on the relationship between interest rate suppression and credit risk. Findings: The results indicate that interest rate suppression negatively affects both the NPL and BDTC ratios, with significant reductions of 0.05% and 0.08%, respectively, for a 1% increase in the suppression index. Financial inclusion reduces the NPL ratio by 0.04% and the BDTC ratio by 0.05% per 1% increase in financial inclusion, contributing to a more stable banking environment. Furthermore, the interaction of interest rate suppression and financial inclusion mitigates credit risks, reducing the NPL ratio by 0.03% and the BDTC ratio by 0.07% for a 1% increase in the interaction term. Conclusion: Interest rate suppression and financial inclusion exhibit contrasting effects on banking stability. While interest rate suppression decreases profitability and alters lending behaviors, financial inclusion mitigates credit risk by diversifying lending practices and expanding access to financial services. Policymakers should prioritize balancing interest rate policies with initiatives to enhance financial inclusion to stabilize and strengthen the banking system.